التّضمين في كتاب أسئلة القرآن المجيد وأجوبتها لزين الدّين الرّازي(ت666ه) (Journal of the College of Basic Education, 2023)
This research aims to find out one of the styles of our Arabic language, which God Almighty has honored by making it the language of the Holy Qur’an. Pronunciations, and it was said: ((They may imbibe a word with meaning and give it its wisdom, and its usefulness is a word performed by two words)).